Mother Tongue Based Education: Critical Reflection of Policy to Practice in Nepal - Limbu, Ambar Jang (ILAM इलम, 2026)
Adopting Nepal’s linguistic diversity, the Constitution of Nepal (2015) has assured constitutional recognition to all mother tongues spoken within the country as national languages. In this context, the primary aim of this study is to discuss which languages have been used as mediums of instruction in Nepal and to examine their current status. This study explores the meaning and importance of mother tongue education. It also examines the legal provisions in relation to the use of mother tongue in education and the actual practical situation of its use in schools and universities. It reviews the achievements of mother tongue education in both informal and formal education, and identifies the challenges observed in practices. This study also asserts ways to improve mother tongue teaching and learning in Nepal. This study employs a qualitative document analysis method to explore how education policies are implemented in practice in Nepal.